PENGARUH PELATIHAN KERJA, PENGEMBANGAN KARIR DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Hikmah, Ivti Lailatul; Sudarsi, Sri (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
In a competitive business environment, organizations need to adopt efficient systems to maintain operational continuity and continue to modernize their operational systems and procedures. Human resource management (HR) is the key to improving the company's overall performance by focusing on managing and improving the quality of HR in all departments. Job training, career development, and organizational culture have an important role in influencing employee potential and performance. This research was conducted to explore the impact of job training, career development and organizational culture variables on employee performance at PT. Srikandi Jaya Property. The data analysis method used is multiple linear regression analysis. The test results show that job training, career development, and organizational culture have a positive and significant effect on employee performance. This confirms that investments in job training, career development, and improving organizational culture can increase overall employee productivity and performance. The research conducted by the author provides important insights for companies to develop more effective HR management strategies, increase employee satisfaction and retention, and strengthen their competitive position in an increasingly complex market. Keywords : Human resource management, Employee training, Career development, Organizational culture, Employee performance